Food Security of Malang City: Before and During the Pandemic of COVID-19 - Rahmawati, Farida; Maharan, Adelia Meydina; Irfansyah, Hafidh; Istiqomah, Triafinna Khoyyun (International Conference on Multidisciplinary Research, 2020)
The COVID-19 pandemic affects all sectors, one of which is food security. As one of the vital needs, food security is an important matter that needs to be prioritized in economic development. This study aims toevaluate the condition of food security before and after the pandemic in Malang City. The variables usedare the number of family members, income before the pandemic, age of the respondent, expenditure for foodneeds, income during the pandemic, and income during the new normal. This study used a quantitativeapproach with data analysis techniques in the form of multiple regression tests, the accuracy test of BLUE(Best Linear Unbiased Estimate) estimation, and classical assumption test. The results showed that in theconditions before the pandemic, the variable age of the respondents had a significant effect on the level offood security, while the variables of the number of family members, income before the pandemic, andexpenditure on food needs had no significant effect on the level of food security. During the pandemic, theincome variable has a significant effect on the level of food security, while the variables for the number offamily members and income during the pandemic have no significant effect on the level of food security inMalang City. The results of this study require further recommendations from relevant stakeholders.Keywords: COVID-19 pandemic, new normal, food security